A 'warm path' for Gulf Stream–troposphere interactions. Issue 1 (1st January 2017) - Sheldon, Luke; Czaja, Arnaud; Vannière, Benoit; Morcrette, Cyril; Sohet, Benoit; Casado, Mathieu; Smith, Doug
Abstract : Warm advection by the Gulf Stream creates a characteristic 'tongue' of warm water leaving a strong imprint on the sea surface temperature (SST) distribution in the western North Atlantic. This study aims at quantifying the climatological impact of this feature on cyclones travelling across this region in winter using a combination of reanalysis data and numerical experiments. It is suggested that the Gulf Stream 'warm tongue' is conducive to enhanced upward motion in cyclones because (i) it helps maintain a high equivalent potential temperature of air parcels at low levels which favors deep ascent in the warm conveyor belt of cyclones and (ii) because the large SST gradients to the north of the warm tongue drive a thermally direct circulation reinforcing and, possibly, destabilizing, the transverse circulation embedded in cyclones. This hypothesis is confirmed by comparing simulations at 12 km resolution from the Met Office Unified Model forced with realistic SST distribution to simulations with an SST distribution from which the Gulf Stream warm tongue was artificially removed or made colder by . It is also supported by a dynamical diagnostic applied to the ERA interim data-set over the wintertime period (1979–2012). The mechanism of oceanic forcing highlighted in this study is associated with near thermal equilibration of low level air masses with SST in the warm sector of cyclones passing over the Gulf Stream warm tongue, which is in sharp contrast to what occurs in their cold sector. It is suggested that this 'warm path' for the climatic impact of the Gulf Stream on the North Atlantic storm-track is not currently represented in climate models because of their coarse horizontal resolution.